The complexities of trans women's access to healthcare in South Africa: moving health systems beyond the gender binary towards gender equity - Siyanda B. Shabalala; Megan M. Campbell (BMC, 2023)
Abstract Background Public health research highlights the influence of socio-political biases shaping obstacles to fair healthcare access based on gender. South Africa has shown commitment to resolving gender imbalances in healthcare, historically emphasizing cisgender women's challenges. However, research gaps exist in exploring how public health systems perpetuate disparities among gender-diverse persons, like trans women, who face exclusion due to their deviation from cisgender norms in healthcare. Critical, intersectionality-informed health research carries the potential to reveal the diversity of gendered healthcare experiences and expose the systems and processes that marginalize trans patients. Methods This study adopts a critical trans politics perspective to explore the socio-political forces limiting South African trans women's access to public healthcare. Using a critical narrative approach, the research asks: 1) What narratives do South African trans women share about their experiences in health systems? 2) What gendered societal structures, practices, and norms enable or hinder their inclusion in health systems? Over a period of two months in 2022, five South African adult trans women between the ages of 22 and 30 participated in 60 to 90-min long, semi-structured individual, telephonic interviews, focusing on participants' subjective experiences in healthcare. Results Trans women's narratives unveiled a culture of medical genderism in South African public healthcare, discriminating against patients whose gender misaligns with societal norms. This culture is represented by the trans women's experiences of their identities being structurally stigmatized and delegitimized when seeking healthcare, reflected in institutional policies, practices, and protocols consistently disregarding and misgendering them. Trans women's systemic erasure was illustrated by the restricted professional knowledge, availability, and adoption of gender-affirming healthcare in a ciscentric public healthcare system prioritizing cisgender needs. The intersection of gender, race, and class dynamics compounded the obstacles faced in accessing healthcare. Conclusions This inquiry underscores the structural hurdles trans women face when accessing suitable public healthcare. It introduces a gender equity framework for trans inclusive healthcare, outlining implications for research, theory, policy, and practice. Toward the goal of embracing complexity and diversity, this framework, for example, promotes the rigorous absorption of trans persons and their healthcare experiences in gender-responsive programming, and encourages the development of a comprehensive understanding of gender equity from an intersectional perspective incorporating the unique needs and rights of trans healthcare seekers. The framework also offers practical guidance for cultivating health systems attuned to gender diversity (such as addressing medical genderism and recognizing the broad spectrum of identity at a policy level).